2005
DOI: 10.2202/1540-8884.1067
|View full text |Cite
|
Sign up to set email alerts
|

Politics and Professional Advancement Among College Faculty

Abstract: This article first examines the ideological composition of American university faculty and then tests whether ideological homogeneity has become self-reinforcing. A randomly based national survey of 1643 faculty members from 183 four-year colleges and universities finds that liberals and Democrats outnumber conservatives and Republicans by large margins, and the differences are not limited to elite universities or to the social sciences and humanities. A multivariate analysis finds that, even after taking into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 1 publication
7
74
0
Order By: Relevance
“…We reasoned that such characteristics, along with others, might also produce an institutional context particularly conducive to the development of liberal political views. For example, liberal arts colleges also focus on academic majors that attract the most liberal faculty-such as the humanities, social sciences, and fine arts (Rothman et al 2005). It also seems reasonable that those academic majors would contribute to attracting more liberal students, who would form a more liberal peer context on campus.…”
Section: Political Partisanship and Higher Educationmentioning
confidence: 99%
“…We reasoned that such characteristics, along with others, might also produce an institutional context particularly conducive to the development of liberal political views. For example, liberal arts colleges also focus on academic majors that attract the most liberal faculty-such as the humanities, social sciences, and fine arts (Rothman et al 2005). It also seems reasonable that those academic majors would contribute to attracting more liberal students, who would form a more liberal peer context on campus.…”
Section: Political Partisanship and Higher Educationmentioning
confidence: 99%
“…Survey data on the politics of the American professorship, varyingly gauged as a function of self-reported ideological labels (for instance, ordinal variables such as "extremely liberal" or "slightly liberal") and party affiliation (predilection for voting in Democratic candidates) display a noticeable tendency towards the political Left [33][34][35][36]. This pattern is even more skewed when we consider the clusters of the humanities and social sciences in isolation, thereby confirming another stereotype about academia in general.…”
Section: Ideological Bias In Contemporary Western Academiamentioning
confidence: 99%
“…Thus, the epistemic appraisal of an x (such as the computational model of an aircraft) must also be guided by the relevant non-epistemic or contextual values such as safety, resilience, acquisition cost, payload capacity, and firepower. Aerospace engineers naturally also want their fluid dynamics to be approximately true 34 or else their aircraft may not kick off the ground (much less reach escape velocity).…”
Section: A Formal Account Of the Relationship Between Philosophical Kmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach provides an opportunity to identify possible issues in the publication and can develop the skills necessary for peer review. Rothman, Lichter, and Nevitte (2005a) presented evidence that conservatives teach at lower-quality colleges and universities than do liberals, even when controlling for faculty achievement. But Ames et al (2005) identified several potential problems in the analysis and presented alternate explanations for the dearth of conservatives in elite academic institutions, such as self-selection into teaching colleges because of a preference for living in areas that have fewer elite schools.…”
Section: Criticize An Article Without Analyzing Datamentioning
confidence: 99%